Pendekatan dalam Supervisi Pendidikan: Analisis Direktif, Non-Direktif, dan Kolaboratif dalam Meningkatkan Profesionalisme Guru - Yunita Febrianti; Mhd Najib Sihab Siregar; Erny Wulandari (Jurnal Zeniusi, 2025)
Educational supervision is an important strategy to improve the quality of learning and the professionalism of educators. There are three main approaches to supervision, namely directive, non-directive, and collaborative. The directive approach places the supervisor as the main provider of direction, suitable for novice teachers or those who need intensive guidance. The non-directive approach emphasizes teacher autonomy in identifying and solving learning problems, so it is suitable for experienced, independent teachers. Meanwhile, the collaborative approach combines the two, emphasizing the partnership between supervisor and teacher in the process of reflection and decision-making. The analysis shows that there is no absolute superior approach. The effectiveness of supervision is largely determined by the suitability of the approach to the characteristics of the teacher, the objectives of supervision, and the educational context. In practice, professional supervisors need to be flexible and able to adjust the approach as needed. The right approach can improve teacher motivation, competence, and performance in managing learning. Therefore, a deep understanding of these three approaches is crucial in implementing effective and sustainable educational supervision.